MZAP—Mobile Application for Basketball Match Tracking and Digitalization of Endgame Reports - Predrag Pecev; Branko Markoski (Applied Sciences)
This paper presents MZAP, a mobile application designed to digitalize basketball match tracking and generate secure, searchable endgame reports. Used by the Basketball League of Serbia, MZAP creates tamper-proof digitally signed records stored as password-protected PDFs with unique UUIDs, digital signatures, and QR codes. Each report is accompanied by a JSON file containing match data, enabling efficient validation through hashed checksums and facilitating data extraction and searchability. The system supports both online and offline modes, bilingual interfaces, mobile and tablet use, and includes features such as WiFi-based monitoring, physical printing, and various sharing options. The solution aims to reduce officials’ working time and increase data accuracy by minimizing human error through structural and UI-level validation methods and real-time monitoring by multiple observers during games. As part of the MZAP software suite, MZAP Converter is under development to support the digitization of legacy paper-based reports using custom CRNN neural networks to optically recognize and digitize historical paper-based reports, bringing them to the same standard as newly created digital ones. The paper also reflects on the broader impact of digital transformation within the Basketball League of Serbia.